Effect of variety and cultivation technology on phenols and antioxidant activity of sweet and sour cherry - Sass-Kiss, A.; Tóth-Markus, M.; Daood, H. G.; Bánáti, D.; Nyéki, J.; Szabó, Z. (International Journal of Horticultural Science, 2010)
The goal of the present work was to compare different sweet and sour cherry cultivars and cultivation methods (bio/integrated) with respect to polyphenol content and antioxidant activity. The concentration of total polyphenols ranged between 880–1050 mg kg-1 of fresh fruit, whereas antioxidant activity expressed as TEAC was found to be between 5.4 and 10.3 mmol kg-1 for the sweet cherry cultivars examined. In case of sour cherry the level of polyphenols ranged between 1283 and 3490 mg/kg fresh edible part of the fruit. Antioxidant activity was recorded between 15–32 mmol kg-1 for the different sour cherry cultivars included in this work. After one-month storage at low temperature, the total phenols and antioxidant activity decreased by 2–40% in the sour cherry cultivars studied. The anthocyanin content in cherry cultivars was less (131–312 mg kg-1) than the135–1893 mg kg-1 found in sour cherries. Anthocyanin level was higher in samples produced under organic farming conditions than in those produced with integrated cultivation.